Effects of precursor particle size on the performance of LiNi0.5Co0.2Mn0.3O2 cathode material. Issue 10 (December 2015) - Nie, Min; Xia, Yun-Fei; Wang, Zhen-Bo; Yu, Fu-Da; Zhang, Yin; Wu, Jin; Wu, Bing
Abstract: Ni0.5 Co0.2 Mn0.3 (OH)2 precursors with different particle sizes and Li2 CO3 were used as the raw materials to synthesis layered structure LiNi0.5 Co0.2 Mn0.3 O2 material in this paper. XRD Rietveld refinement, BET specific surface area (SSA) analysis, particle distribution analysis and other electrochemical tests were performed to determine the effects of particle size on the performance of LiNi0.5 Co0.2 Mn0.3 O2 material. Physical and electrochemical characterizations demonstrate that sample NCM523-D3 (3 μm) has the best layered structure, and with the decrease in precursor particle size, the cation mixing degree shows up a decrease trend while the specific surface area increases from 0.236 m 2  g −1 to 0.937 m 2  g −1 . Sample NCM523-D3 presents a better rate capability than NCM523-D6 and -D9, whose average capacity for 1 C, 2 C, 5 C and 10 C reaches 155.7, 145.1, 128.2 and 97.5 mA h g −1, respectively. Although the CV and EIS tests show that NCM523-D3 has the maximal impedance among all samples, but the bigger crystallite dimension and larger SSA of NCM523-D3 are the key factors affecting the outstanding capacity and rate performance of the material.